PENGARUH PERBANDINGAN MEDIA TANAM DAN KONSENTRASI PUPUK PLANT CATALYST 2006 TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PRENURSERY - Subhan Nur Nasution (JURNAL AGROPLASMA, 2019)
Palm oil is quite important commodities in Indonesia and still have a bright prospect.Success in oil palm breeding depends on the ratio of growing media and fertilizer on a regular basis starting from the early seedling stage. For that a study This study was conducted in Village Pangkatan C, Labuhanbatu District, with altitude of ± 50 meters above sea level. The study used randomized block design with 2 factors that comparisons planting medium consisted of four levels ie M0 = Top Soil (Control), M1 = Top soil, manure (3: 1), M2 = Top soil, sand (3: 1) and M3 = Top soil, manure, sand (3: 1: 1). Plant fertilizer concentrations Catalyst 2006 consists of four levels ie C0 = 0 grams / liter of water (control), C1 = 1 gram / liter of water, C2 = 2 grams / liter of water and C3 = 3 grams / liter of water. Parameters measured were seedling height, stem diameter, number of leaves, leaf length, leaf area and total wet weight of the seeds.The result showed that treatment comparison planting medium high influence on seedling ages of 30, 60 and 90 days after planting, leaf number and fresh weight of seedlings. Plant fertilizer concentrations Catalyst 2006 gives effect to the plant height age 60 and 90 days after planting, stem diameter age of 90 (After deay planting), number of leaves, and the weight of wet seeds. While the interaction between treatment comparisons of growing media and fertilizer concentrations Plant Catalyst 2006 paramerter only real effect on plant height at 30 (After deay planting). Keywords : Comparison of Growing Media, Fertilizer Catalyst 2006, oil palm seedlings.